Composite Vascularized Autograft Elbow Transplant: A Case Report. Issue 3 (July 2021) - Pathak, Neil; Sides, Eric E.; Piper, Samantha L.; Lee, Charles K.; Hansen, Scott L.; Terry, Michael J.; Lattanza, Lisa L.
Abstract : Case: A 37-year-old man presented with an absent right elbow joint secondary to trauma, subsequent ankylosis, total elbow arthroplasty (TEA), and TEA explantation after infection. The patient also had a contralateral complete brachial plexus injury, but an intact elbow joint. Given that the patient had a functional right hand/wrist, composite vascularized autograft elbow transplant was performed from left to right upper extremity. Four years postoperatively, the patient could independently complete activities of daily living. Conclusion: This case is the first to report composite vascularized autograft elbow transplant. Although indications are limited, this case illuminates novel uses of standard techniques for a difficult problem.